Die logos-leer van Filo van Aleksandrie : 'n kultuur-historiese ondersoek - Van Schalkwyk, C. H. J., 1971- (Stellenbosch : University of Stellenbosch, 2011)
Thesis (DPhil)--University of Stellenbosch, 2004.